INTEGRATED REMOTE AND GEOPHYSICAL METHODS FOR SEARCHING DEPOSITS OF HYDROCARBONS (TERRITORY OF THE CENTRAL CAUCASUS CAUCASUS) - V. M. Kharchenko; D. V. Lapta; A. E. Nerkararyan (Наука. Инновации. Технологии)
Introduction: the relevance of researching a complex of remote and geophysical methods for searching for hydrocarbon deposits is due to the need to increase the efficiency of not only prospecting and exploration, but also the development of existing oil and gas fields in Russia. The research provided will help in identifying new hydrocarbon deposits, as well as relatively reduce the costs of their exploration. Materials and research methods: the starting materials and methods of these studies are a comprehensive interpretation of the Nurin-Hag ring cosmophotomalancies (CCFA) in Kalmykia [4]. And also, the materials of the work «Creating a digital model of the gravitational and magnetic fields of the territory of the Ciscaucasia» [2]. Research results and discussion: as a result of the interpretation of the research data, new results are shown on integrated remote and geophysical methods for searching for hydrocarbon deposits and identifying the most promising territories using the territory of the Central Ciscaucasia as an example. Conclusions: An operational, thoroughly reasoned and economically feasible forecast of hydrocarbon accumulations is currently unthinkable without the use of a complex of magnetic and gravitational methods. These methods are becoming not only integral, but also the irst link in the search for oil and gas in various regions of the country and the world.